(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Poverty is a pervasive issue that continues to plague societies worldwide, affecting millions of individuals and families. It is a complex phenomenon with multifaceted causes, including economic, social, and environmental factors. The prevalence of poverty has far-reaching implications, impacting various aspects of people’s lives, such as access to education, healthcare, and opportunities for upward mobility. Despite efforts from governments, NGOs, and international organizations to address poverty through policies and programs, the problem persists, highlighting the need for a more comprehensive and sustainable approach. In this research, we will delve into the root causes of poverty, examine the impact it has on individuals and societies, and explore potential solutions to alleviate poverty and create a more equitable world. By understanding the complexities of poverty and its consequences, we can work towards meaningful change and improve the quality of life for those affected by this global challenge.